KEGIATAN SOSIAL KEAGAMAAN KOMUNITAS DAKWAH DI MASA COVID-19 (Studi Atas Pengalaman Pengurus Komunitas Sedekah Berjamaah Yogyakarta) - Ahmad Putra (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2021)
This research discusses the implementation of socio-religious activities carried out by the Yogyakarta congregational alms community during the covid-19 period. The success of the community in carrying out activities is of course determined by the existing movers and administrators, so that activities can still be carried out even though the pandemic has not ended. This research is a qualitative research with a phenomenological approach, meaning that the information the writer gets is really from the direct experience of the administrators of the alms community in the Yogyakarta congregation in carrying out socio-religious activities. As for activities carried out during a pandemic, such as distributing boxed rice to people who deserve assistance and holding religious studies once a week. Along with all that, still every activity carried out raises anxiety for all community administrators and members about the danger of the spread of covid-19 because in every activity they always meet with the public at large